Relating the Growth Phenology and Biomass Allocation in Seedlings of 13 Acadian Tree Species With Their Drought Tolerance - Pearson, Erin; D’Orangeville, Loïc (Frontiers in Forests and Global Change, 2022)
Climate models predict an increase in the frequency and intensity of drought events in the Acadian Forest Region, with higher risk of tree growth decline and mortality. To accurately predict future species response, we need to better compare drought-coping traits between Acadian tree species, especially at early life stages as young trees tend to display increased sensitivity to small environmental changes than mature trees. Here, we compared the seasonal growth phenology and biomass allocation in seedlings of 13 Acadian tree species in a controlled environment with their commonto assess their ability to predict species drought tolerance rankings. We focused on two traits associated with drought tolerance, namely biomass allocation to root systems, which affects water uptake, and phenology of seasonal growth, where earlier growth can avoid the peak drought period in late summer. We find an earlier onset of height growth in drought-tolerant species (P<0.05), supporting the late-summer drought avoidance hypothesis. The observed biomass allocation patterns did not support the hypothesis of a higher allocation to roots with drought tolerance. In fact, we report an initially higher shoot-to-root ratio in drought tolerant species (P<0.05), which becomes non-significant as the season progresses. Our results highlight the complexity of drought response strategies, as the developmental traits reported here only account for a fraction of each species overall drought tolerance. Yet, the important differences in growth phenology observed here between species, and their linkage with drought tolerance indices, could help predict species response to future drought regime.